Long COVID Experiences, Management and Outcomes of Patients with Post Coronavirus 2019 - Khongphoenoy, Angkhana; Buatee, Supatra; Wongpiriyayothar, Apinya (Journal of The Royal Thai Army Nurses, 2025)
The purpose of this descriptive research was to study Symptom experiences, management and outcomes long COVID among Patients infected with the coronavirus 2019 confirmed by the ATK or RT PCR test results and pneumonia. One hundred and four patients who were admitted at Chaturas Hospital, Chaiyaphum Province between June and December 31, 2022. The instrument was a questionnaire on residual symptom management in patients after COVID-19 infection. Frequency, percentage, mean and standard deviation were used to analyzed the data. The participants aged between 22 and 92 years old, with the majority being female. The symptom experience was as follows: 1. The first five of Long COVID symptoms was 1) weakness 2) cough 3) muscle and joint pain 4) fatigue 5) dizziness. The first three of frequency of Long COVID was 1) muscle and joint pain, 2) increased hair loss, 3) weakness. The first three of severity was 1) muscle and joint pain 2) cough 3) weakness and the first three of Distress of Long COVID was 1) muscle pain and joint pain, 2) increased hair loss, 3) weakness.; 2. Most of symptom management strategies and outcomes was having a rest, asked for help from others and taking medication. It is recommended that health care providers should assess the experiences in order to delivery comprehensive symptom management recommendations. Comprehensive symptom management not only reduce the impact of symptoms but also help individuals live as normal as possible.